2002
DOI: 10.1046/j.1365-3148.2002.00373.x
|View full text |Cite
|
Sign up to set email alerts
|

Structural characterization of the epitope recognized by the new anti‐Fy6 monoclonal antibody NaM185‐2C3

Abstract: The epitope recognized by a new anti-Fy6 monoclonal antibody (MoAb) (clone name: NaM185-2C3) was characterized using peptides synthesized on pins (Epitope scanning kit). The clone was obtained from splenocytes of mice immunized with CHO cells expressing the recombinant Duffy glycoprotein. NaM185-2C3 recognized a linear epitope, the essential portion of which was pentapeptide Phe-Glu-Asp-Val-Trp comprising amino acid residues 22-26 of the main (336aa) isoform of the Duffy antigen. All the amino acid residues of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
0
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(42 citation statements)
references
References 35 publications
1
40
0
1
Order By: Relevance
“…(Tournamille et al 1998;Yazdanbakhsh et al 2000). Because the Fy x polymorphism results from a point mutation within the coding region of the Duffy gene, the nonerythroid cells should also show reduced expression and chemokine binding (Olsson et al 1998;Parasol et al 1998;Tournamille et al 1998;Wasniowska et al 2002).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(Tournamille et al 1998;Yazdanbakhsh et al 2000). Because the Fy x polymorphism results from a point mutation within the coding region of the Duffy gene, the nonerythroid cells should also show reduced expression and chemokine binding (Olsson et al 1998;Parasol et al 1998;Tournamille et al 1998;Wasniowska et al 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Endogeous peroxidases and biotin were blocked using 3% H 2 O 2 in methanol and an avidinbiotin blocking kit (Vector Labs). The specificity of MAb ␣ Fy6 (clone 2C3) used in this study was determined by immunoblotting, and epitope mapping showed that it binds to the epitope 24 FEDVW 28 located on the amino-terminal extracellular domain of the Duffy glycoprotein (Segerer et al 2000;Wasniowska et al 2002). An irrelevant monoclonal IgG 1 isotype antibody (Dako Diagnostics; Glostrup, Denmark) was used as the control primary antibody.…”
Section: Immunohistochemistrymentioning
confidence: 99%
“…555445; BD Biosciences Pharmingen, Franklin Lakes, NJ), RPE-Cy5.1-conjugated mouse monoclonal anti-CD45 (catalog no. PM IM2653; Beckman Coulter, Inc., Fullerton, CA), mouse clone 2C3 anti-Duffy blood group antigen receptor for chemokines (DARC)/Fy (kindly provided by Dr. Ives Colin; INSERM, Institute National de Transfusion Sanguine, Paris 5,6 ), mouse monoclonal anti-CCL27 (catalog no. MAB3761; R&D Systems, Minneapolis, MN), neutralizing rat anti-CCL27 antibody (clone 68623; catalog no.…”
Section: Antibodiesmentioning
confidence: 99%
“…Cultures were incubated at 37°C for at least 24 hours, which allowed the merozoites to reinvade fresh RBCs. Blockade of RBC invasion was assayed by using different antibodies and a chemokine against human DARC: anti-FY6 2C3 25 at 20 mg/mL, antiFyB (Abcam) at 25 mg/mL, and the chemokine interleukin-8 (CXCL-8/IL-8) (Peprotech Asia) at 1000 nM. The overall experimental scheme is shown in Figure 1.…”
Section: Invasion Assaymentioning
confidence: 99%